Streptococcus Group B contamination of the birth canal in pregnant women: the relevance of the introduction of screening programs - S. A. Levakov; E. K. Borovkova (Акушерство, гинекология и репродукция)
The aim of the study was to determine the frequency of occurrence of group B Streptococcus in women in labour and newborn babies. Materials and methods. prospective study included two groups: group 1 patients (n=35) with full-term pregnancy and term birth, group 2 patients (n=22) with preterm birth in the period from 34 to 37 weeks. All patients upon admission and all newborns was carried out rapid test for Streptococcus group B. Results. in the 1st group, the test was positive in 25.7% of women and 8.6% of newborns. In the 2nd group, the test was positive in 18.2% of women and 22.7% of newborns.a prospective study was conducted of contamination of the genital tract in pregnancy Streptococcus group B. We have formed 2 groups: group 1 patients (n=35) with full-term pregnancy and term birth, group 2 (n=22) patients with preterm birth in the period from 34 to 37 weeks. All patients upon admission and all newborns was conducted rapid test for Streptococcus group B. In the 1st group, the test was positive in 25.7% of women and 8.6% of newborns. In the 2nd group, the test was positive in 18.2% of women and 22.7% of newborns.